Evaluation of population dynamics of Macrobrachium olfersii (Palaemonidae) along ~150 km extension of the Lower Ribeira de Iguape River, São Paulo, Brazil - Ribeiro, Crislene C. [UNESP]; Braga, Adriane A.; Miranda, Esthephany K. S. [UNESP]; Bertini, Giovana [UNESP] (Instituto de Ecologia y Ciencias Ambientales (IECA), 2023)
This study aimed to verify the spatial and temporal population parameters of Macrobrachium olfersii over of ~150 km of the Ribeira de Iguape River (SP). Prawns were collected monthly (January to December 2007) in Eldorado, Sete Barras, Registro, and Iguape, using traps and sieves. We analyzed 9,691 individuals with carapace length (CL) from 2.2 to 25.4mm. In our results, smaller individuals were found close to the estuary, i.e., Iguape, whereas larger individuals were recorded as they moved away from the estuary. Reproduction was continuous but more intense in the summer, when temperature and rainfall were higher. The total sex ratio differed from the expected favoring males (1:0.73), and this deviation was also observed in Eldorado, Registro, and Iguape. Female sexual maturity was at 10.9 mm CL, without significant variation along the river. The regions closer to the estuary (Iguape/ Registro) presented lower CL and longevity, and higher k, due to the greater number of juveniles. In conclusion, the results suggest that the variation in size, recruitment, sexual maturity, and growth of individuals are related to the population structure along ~150 km of the river, and are triggered by the upstream migration of juveniles after larval development, which takes place in the estuarine region
Keywords: longevity; sex ratio; sexual maturity; upstream migration; Vale do Ribeira